Analyses of the neandertal patellae from El Sidrón (Asturias, Spain) with implications for the evolution of body form in Homo. Issue 141 (April 2020) - Rosas, Antonio; Losada Agustina, Beatriz; García-Martínez, Daniel; Torres-Tamayo, Nicole; García-Tabernero, Antonio; Pastor, Juan Francisco; Rasilla, Marco de la; Bastir, Markus
Abstract: The evolution of the body form in Homo and its potential morphological connection to the arrangement of different skeletal systems is of major interest in human evolution. Patella morphology as part of the knee is potentially influenced by body form. Here, we describe for the first time the patellae remains recovered at El Sidrón Neandertal site and analyze them in a comparative evolutionary framework. We aim to clarify whether morphometric features frequently observed in Neandertal and modern human patellae are retained from a primitive anatomical arrangement or whether they represent derived features (apomorphies). For this purpose, we combine analyses of discrete features, classic anthropological measurements, and 3D geometric morphometrics based on generalized Procrustes analysis, mean size and shape comparisons, and principal components analysis. We found a size increment of the patella in hominin evolution, with large species showing a larger patella. Modern humans and Neandertals exhibit overall larger patellae, with maximum values observed in the latter, likely as a consequence of their broader body shape. Also, some Neandertals display a thicker patella, which has been linked to larger quadriceps muscles. However, Neandertals retain a primitive morphology in their patellar articular surfaces, with similar-sized lateral and medial articular facets, leading to a more symmetrical internal face. This feature is inherited from a primitive Homo ancestor and suggests a different configuration of the knee in Neandertals. Conversely, Homo sapiens exhibits an autoapomorphic patellar anatomy with expanded lateral articular facets. We propose that these distinct configurations of the patella within Homo may be a consequence of different body forms rather than specific functional adaptations of the knee. Thus, the slender body form of modern humans may entail a medial reorientation of the tibial tuberosity (patellar ligament), allowing lateral surface expansion. These anatomical evolutionary variations may involve subtle secondary differences in bipedalism within Homo .